Learning from gesture How our hands change our minds - Novack, Miriam (Educational psychology review, 2015)
When people talk, they gesture, and those gestures often reveal information that cannot be found in speech. Learners are no exception. A learner's gestures can index moments of conceptual instability, and teachers can make use of those gestures to gain access into a student's thinking. Learners can also discover novel ideas from the gestures they produce during a lesson, or from the gestures they see their teachers produce. Gesture thus has the power not only to reflect a learner's understanding of a problem, but also to change that understanding. This review explores how gesture supports learning across development, and ends by offering suggestions for ways in which gesture can be recruited in educational settings